Evidence for Palaeozoic orthoconic cephalopods with bimineralic shells. (30th November 2017) - De Baets, Kenneth; Munnecke, Axel
Abstract: Based on the aragonite composition of extant and exceptionally preserved fossil cephalopods going back to the early Palaeozoic, it is commonly assumed that all externally shelled cephalopods had an aragonitic shell wall. We demonstrate herein that at least two taxa of Siluro‐Devonian orthoconic nautiloids ( Dawsonoceras, Spyroceras ) had an original bimineralic shell, which developed convergently with gastropods and bivalves.